Correlation between sensory and instrumental measurements of saltiness in Queso Molido Narinense - Juan Sebastián Ramírez-Navas; Victor Alexander Aristizabal-Ferreira; Jessica Aguirre-Londoño; Sandra Patricia Castro-Narváez (Revista Facultad de Ingeniería Universidad de Antioquia, 2021)
A sensory study was conducted at the Universidad Santiago de Cali with Queso Molido Nariñense. To determine the preferred levels of concentration acceptable by consumers, samples were made with different concentrations of NaCl (C1 = 0.62%, C2 = 0.87%, C3 = 1.05%, C4 = 1.74%, C5 = 2.71%, and C6 = 5.34%). The results show that sample C4 had the highest degree of acceptance, followed by C2, C3, and C5, while C1 and C6 had the lowest acceptance. Consumers were able to distinguish salt differences above 0.27%. It was possible to predict consumer reaction regarding their levels of acceptability and perception using the Sensory-Instrumental correlation. This result showed that either an extremely low or a very high level of concentration of salt in cheese could result in a low acceptance by consumers.